Phase 2b Study of Pimodivir (JNJ-63623872) as Monotherapy or in Combination With Oseltamivir for Treatment of Acute Uncomplicated Seasonal Influenza A: TOPAZ Trial. (14th November 2018) - Finberg, Robert W; Lanno, Riin; Anderson, David; Fleischhackl, Roman; van Duijnhoven, Wilbert; Kauffman, Robert S; Kosoglou, Teddy; Vingerhoets, Johan; Leopold, Lorant
Abstract: Background: Pimodivir, a first-in-class inhibitor of influenza virus polymerase basic protein 2, is being developed for hospitalized and high-risk patients with influenza A. Methods: In this double-blinded phase 2b study, adults with acute uncomplicated influenza A were randomized 1:1:1:1 to receive one of the following treatments twice daily for 5 days: placebo, pimodivir 300 mg or 600 mg, or pimodivir 600 mg plus oseltamivir 75 mg. Antiviral activity, safety, and pharmacokinetics of pimodivir alone or in combination were evaluated. Results: Of 292 patients randomized, 223 were treated and had confirmed influenza A virus infection. The trial was stopped early because the primary end point was met; the area under the curve of the viral load, determined by quantitative reverse transcription–polymerase chain reaction analysis, in nasal secretions from baseline to day 8 significantly decreased in the active treatment groups, compared with the placebo group (300 mg group, −3.6 day*log10 copies/mL [95% confidence interval CI, −7.1 to −0.1]; 600 mg group, −4.5 [95%CI −8.0 to −1.0]; and combination group, −8.6 [95% CI, −12.0 to −5.1]). Pimodivir plus oseltamivir yielded a significantly lower viral load titer over time than placebo and a trend for a shorter time to symptom resolution than placebo. Pimodivir plasma concentrations increased in a dose-proportional manner. The most commonly reported adverse event was mild or moderate diarrhea. Conclusions: Pimodivir (with or without oseltamivir) resulted in significant virologic improvements over placebo, demonstrated trends in clinical improvement, and was well tolerated. Pimodivir 600 mg twice daily is in further development. Clinical Trials Registration: NCT02342249, 2014-004068-39, and CR107745. Abstract : Pimodivir is a first-in-class inhibitor of the influenza virus polymerase basic protein 2. This dose-ranging study was designed to evaluate the efficacy and safety of pimodivir in patients with naturally acquired influenza A virus infection and to evaluate the optimal dose for further development.